Answer:
c
d
Step-by-step explanation:
You show the text of the problem, but you need to show the figure too.
Answer:
see explanation
Step-by-step explanation:
Assuming you are factoring the expression
Given
4y² + 26y + 30 ← factor out 2 from each term
= 2(2y² + 13y + 15) ← factor the quadratic
Consider the factors of the product of the coefficient of the y² term and the constant term which sum to give the coefficient of the y- term.
product = 2 × 15 = 30 and sum = 13
the factors are 10 and 3
Use these factors to split the y- term
2y² + 10y + 3y + 15 ( factor the first/second and third/fourth terms )
= 2y(y + 5) + 3(y + 5) ← factor out (y + 5) from each term
= (y + 5)(2y + 3)
Thus
4y² + 26y + 30
= 2(y + 5)(2y + 3)
The factors for given equation f(x)=
.
- (x-1) - No
- (x-3) - No
- (x+3) - Yes
- (x-5) - Yes
- (x+5) - Yes
<u>Step-by-step explanation:</u>
The given equation is f(x)=
.
Add 0 at the end of the equation.
= 0.
Let us group the given equation,
=0.
⇒ Group 1:
.
Group 2:
.
Pull out factor from each group,
⇒ Group 1:
.
Group 2: (x+3) (-25).
Join the two group since both (x+3) is common in both groups.
=0.
One of the factor is (x+3).
Other factors are solved by the formula,
.
= (x+5) (x-5) .
The other factors are (x+5) and (x-5).